Development of Guided Invention Based Learning Tools on Circle Material to Facilitate Mathematical Comprehension Ability of Class VI SD / MI - Lestari, Ayu Dwi; Kartini, Kartini; Zulkarnain, Zulkarnain (Journal of Educational Sciences, 2021)
This research was motivated by the lack of teachers in developing learning tools causing students' mathematical understanding is still in the low category. The learning devices used in schools have not trained students' mathematical understanding skills. The aim of this study is to produce guided discovery-based mathematics learning tools to facilitate mathematical comprehension skills that meet the validity and practicality requirements. This type of research was a development research using the ADDIE model. The instruments used in this study were the syllabus validation instrument, lesson plans, student worksheet and practicality using student response questionnaires. Based on the results of data analysis, it shows that the guided discovery-based mathematics learning device is a valid category. The results of the validation of the syllabus, RPP and LKPD showed that the category was very valid with the value sequentially obtaining a score of 92.5%; 95%; and 94.87%. The results of the practicality data analysis in small group trials showed a very practical category with a score of 93.64%. It can be concluded that the learning tools developed are feasible and practical to use in the learning process.